A study on the pathogenesis of Trypanosoma evansi in buffaloes, Holstein Friesian and Ongole cattle - S. Partoutomo; M. Soleh; F. Politedy; A. Day; A.J. Wilson; D.B. Copeman (Jurnal Ilmu Ternak dan Veteriner, 1995)
A study on the pathogenesis of Trypanosoma evawi was carried out in 5 buffalo calves and 5 buffalo adults, 6 Holstein-Friesian calves and 6 Holstein-Friesian adults, and 6 Ongole calves and 6 Ongole adults, each ofwhich was divided into 3 infected and 2 uninfected buffalo calves and adults, and 3 infected and 3 uninfected calves and adults of Holstein Friesians and Ongoles. None of infected animals showed acute clinical signs along the course of the observation period, however roughness of the hair and skin, emaciation, weakness and loss of weight gains were the common clinical signs. Clinical signs of calves were more severe than adults, and those of buffaloes were more severe than cattle . Gross pathological changes were not specific . The mortality rate was 2/3 in buffalo calves, 1/3 in Holstein-Friesian calves and 1/3 in Ongole calves . None of infected adults died of infection. Buffaloes had longer and higher parasitemia than Holstein-Friesians or Ongoles. Erythrocyte counts of infected animals decreased to lower levels than controls, however they fluctuated in the normal values . Haemoglobin and PCV values of infected animals were significantly lower than those of non-infected controls, and those of calves were more severe than adults, and those of buffaloes were more severe than cattle . Infections resulted in loss of weight gains which was the greatest in buffaloes then followed by Holstein-Frisians and finally Ongoles.